Influence Disclosure of Sustainability Report on Company Value with Profitability As a Moderate for Companies Listed in the SRI – KEHATI Stock Index for the 2020 - 2022 Period - Aimatul Yumna (Devitara Innovations, 2024)
This research aims to empirically prove the effect of sustainability report disclosure on company value with use profitability as variable moderation as well as size company and leverage as variable control. This research is quantitative research using secondary data obtained from the company's annual report and the company's sustainability reporting report. The population in this study are companies that are members of the SRI - KEHATI stock index from 2020-2022. The number of samples used in this research was 47 data. The data analysis technique used is Moderate Regression Analysis with the software used for data processing is SPSS version 2.3. Based on the results of the analysis, it is known that the sustainability report has a negative effect on mark company, and profitability No moderate connection between sustainability reports and mark company.